PERANAN DINAS PARIWISATA DALAM MEMPROMOSIKAN OBJEK WISATA GUNA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) - Herru Prasetya Widodo (REFORMASI, 2011)
Regional income (PAD) and sources that support it has always been a problematic issue not only in the past but also in the present when the demands for regional autonomy is always developed. Tourism plays a very important and strategic for the national economy, it is evident by the increase in national income, regional income and foreign exchange. In addition, tourism is also set as one of the substitute non renewable-commodity, such as oil and mining. In order to optimize the role of tourism office was then considered very necessary and urgent to set up mechanisms in conceptual development of tourism that can be used as guidelines in determining the direction, goals, objectives and policy strategies for tourism development in Indonesia.